Nucleation and growth of Fe-rich phases in Al-5Ti-1B modified Al-Fe alloys investigated using synchrotron X-ray imaging and electron microscopy. (30th July 2021) - Zhao, Yuliang; Zhang, Weiwen; Song, Dongfu; Lin, Bo; Shen, Fanghua; Zheng, Donghai; Xie, ChunXiao; Sun, Zhenzhong; Fu, Yanan; Li, Runxia
Highlights: Al-5Ti-1B and applied pressure reduced the size and number of primary Al3 Fe phases. Al-5Ti-1B changes the 3D morphology of primary Al3 Fe from rod-like to plate-like. Al-5Ti-1B improves the growth rate of primary Al3 Fe and their branching ability. Experimental results show that TiB2 provides possible nucleation sites for Al6 Fe. Abstract: Plate-like Fe-rich intermetallic phases directly influence the mechanical properties of recycled Al alloys; thus, many attempts have been made to modify the morphology of these phases. Through synchrotron X-ray imaging and electron microscopy, the underlying nucleation and growth mechanisms of Fe-rich phases during the solidification of Al-5Ti-1B-modified Al-2Fe alloys were revealed in this study. The results showed that the Al-5Ti-1B grain refiner as well as the applied pressure both resulted in reduction of the size and number of primary Al3 Fe phases and promoted the formation of eutectic Al6 Fe phases. The tomography results demonstrated that Al-5Ti-1B changed the three-dimensional (3D) morphology of primary Fe-rich phases from rod-like to branched plate-like, while a reduction in their thickness and size was also observed. This was attributed to the fact that Ti-containing solutes in the melts inhibit the diffusion of Fe atoms and the Al3 Fe twins produce re-entrant corner on the twin boundaries along the growth direction. Moreover, the TiB2 provides possible nucleation sites for Al6 Fe phases. The nucleation mechanism of Fe-rich phases is discussed in terms of experimental observations and crystallography calculations. The decrease in the lattice mismatch between TiB2 and Al6 Fe phases was suggested, which promoted the transformation of Al3 Fe to Al6 Fe phases.